Current-tunable current-mode multifunction filter employing a modified CCCCTA - Kumngern, Montree; Torteanchai, Usa; Sarsitthithum, Kanok (My University, 2012)
This paper presents a current-tunable current-mode universal biquadratic filter with two inputs and two outputs using one modified current-controlled current differencing transconductance amplifier, two grounded capacitors and one grounded resistor. The proposed circuit provides following advantages: realization of low-pass, band-pass, high-pass, band-stop and all-pass current responses; orthogonal control of the natural frequency and the quality factor; employment of grounded passive components which is suitable for integrated circuit implementation and low active and passive sensitivities. Simulation results are given to confirm the presented theory. © 2012 IEEE.
Keywords: biquad filter; current-mode circuit; modified current-controlled current conveyor transconductance amplifier